Hubungan Kadar Ureum terhadap Restless Legs Syndrome pada Pasien Chronic Kidney Disease: Relationship between Ureum Level and Restless Legs Syndrome in Patients with Chronic Kidney Disease - Gusri Rahayu; Hema Malini; Elvi Oktarina (Fakultas Keperawatan Universitas Andalas, 2019)
Chronic Kidney Disease (CKD) is a condition where the body fails to maintain metabolism and fluid and electrolyte balance to cause uremia. Chronic Kidney Disease requires renal replacement therapy in the form of dialysis and kidney transplantation. The aim of this study is to prove the relationship the ureum level value with Restless Legs Syndrome in Chronic Kidney Disease Patients. Long-term hemodialysis and uremia can cause various neurological complications such as Restless Legs Syndrome (RLS). The instrument used in this research measured the severity RLS using The International Restless Legs Syndrome Questioner. This study is a correlation analysis using a cross sectional study design with a sampling technique that is purposive sampling of 16 hemodialysis patients. Data were analyzed using pearson correlation test. The results showed that there was a correlation between urea level and severity of Restless Legs Syndrome in Chronic Kidney Disease patients with p value (0,028). There is a need for training and monitoring of urea levels in an effort to improve the severity of RLS.